Flexible Working Arrangement and Well-Being amongst Private University Employees: A Pilot Study - Nugraha, Fida Nirmala; Aisha, Atya Nur; Suwarsono, Litasari Widyastuti (International Journal of Innovation in Enterprise System, 2025)
The COVID-19 epidemic led to several adjustments in the workplace. Working from home or having flexible arrangements (FWA) has become standard practice in many workplaces. A Bandung-based private institution implemented a similar setup. FWA practices, tenure, and gender, as well as the combination of the three, had a substantial impact on the relationship dimension of subjective well-being. The association between the influence of FWA on the relational dimension of subjective well-being is strengthened by the effects of tenure and gender. This indicates that in this case where respondent used FWA, had a longer tenure, and is the same gender as his or her co-workers, they positively interact with other individuals (in a work setting, according to the context of this research). With the addition of other criteria (tenure and gender), the favorable perspective on the relationship of subjective well-being was amplified. FWA practices generated a positive perception of subjective well-being.